MODEL PENDIDIKAN KARAKTER UNTUKSEKOLAH MENENGAH KEJURUAN (SMK) DI KOTA YOGYAKARTA - dan Rahmah Tyasari, Untung Kurniawan, Doni Sarosa, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This study aims to determine the manufacture of the formulation of a model for charactereducation Vocational School (SMK) in Yogyakarta by using norms and local knowledge of Yogyakarta.This research is a qualitative descriptive study. This research was conducted in N 2, SMKN 3,and SMK Piri Yogyakarta. The mechanisms used to achieve the creation of character educationformula is: (1) Conducting research literature, (2) Conducting interviews, (3) formulate a model ofcharacter education. The formula for vocational education character created by norms approach andlocal knowledge of Yogyakarta. The instrument used to obtain data is a list of interview question.Interviews were conducted to obtain information about the condition of the character / personalityof vocational students, school effort in improving the character of vocational students, opinionsabout the objectives, contents, methods, tools and design environment model of charactereducation.The formulation of the character education model consists of objectives, contents, methods,environments, tools, educators, and students in character education. The purpose of CharacterEducation is in accordance with national education goals. The contents of character education arethe values that exist at the school environment, and skills provided by educators in order to establishgood character on the learner. The method consists of character education character educationimplementation and maintenance of noble character who has been embedded in students' self.Character education environment consists of a family environment, schools, and youth organizations.Character education tool consisting of educational tools that are actions such as praise, reprimand,and an educational tool that is material such as character education module. Educators in thecharacter education teachers, school' staff, and parents. Students in character education are allstudents at the Vocational School (SMK).Keywords: character education, norms, local knowledge